Case Report: Extremely elevated ascitic fluid amylase as a diagnostic clue for peritoneal mucormycosis caused by Rhizopus microsporus following exertional heatstroke - Guanghui Chen; Haibo Lei; Guyi Wang; Yanyan Zhou (Frontiers in Medicine, 2026)
Background Mucormycosis is a rapidly progressive, life-threatening fungal infection that typically affects immunocompromised hosts. Disseminated peritoneal mucormycosis is extremely rare and often diagnosed late. Heatstroke is an under-recognized predisposing condition. Case presentation A 54-year-old male brickworker developed peritoneal mucormycosis caused by Rhizopus microsporus following exertional heatstroke. On day 11 after heatstroke, he developed massive ascites. Ascitic fluid amylase was markedly elevated to 51,808 U/L, while plasma amylase remained low (40.3 U/L). Contrast study excluded perforation, and CT showed a normal pancreas. Sputum fungal culture grew Rhizopus species on day 4. Targeted next-generation sequencing (tNGS) of ascitic fluid and blood identified R. microsporus (151 and 53 reads). Tissue biopsy was precluded by severe coagulopathy and thrombocytopenia. The patient received liposomal amphotericin B (L-AmB) plus isavuconazole; subsequent detection of Candida tropicalis superinfection prompted a switch to caspofungin while continuing L-AmB. Ascitic fluid amylase declined progressively to 38 U/L, with radiological resolution. The patient recovered without surgical debridement. Conclusion Extremely elevated ascitic fluid amylase with a normal pancreas and excluded perforation should prompt consideration of peritoneal mucormycosis. This case suggests that fungal-derived enzymes may contribute to the enzyme elevation, though this remains speculative without direct assays. Combination antifungal therapy achieved cure despite contraindications to surgery. Heatstroke is an important but under-recognized risk factor for disseminated mucormycosis.